2013
DOI: 10.1038/nsmb.2640
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylation site–induced decay of upstream transcripts enforces promoter directionality

Abstract: Ntini et al. 3The non-protein-coding part of the human genome is pervasively transcribed into a large diversity of non-coding (nc) RNA 1 . A substantial fraction of this material derives from, or near, active gene promoters, that are producing a range of small-( 1-6 ) and long non-coding RNA (lncRNA) 7 . Indeed, it has been estimated that >60% of lncRNAs in human embryonic stem cells derive from promoters of active proteincoding genes 8 . Although some lncRNAs have reported functions, these species are genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
351
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 265 publications
(375 citation statements)
references
References 39 publications
22
351
1
1
Order By: Relevance
“…However, some aspects of Su(s)-Wdr82-dependent regulation differ from these other processes. For example, it appears that cryptic, canonical pA signals can mediate promoter-proximal termination and degradation of PROMPTs (Ntini et al 2013). However, the unstable αβ RNAs acquire poly(A) tails by a mechanism that is independent of the canonical pA signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some aspects of Su(s)-Wdr82-dependent regulation differ from these other processes. For example, it appears that cryptic, canonical pA signals can mediate promoter-proximal termination and degradation of PROMPTs (Ntini et al 2013). However, the unstable αβ RNAs acquire poly(A) tails by a mechanism that is independent of the canonical pA signal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, short, polyadenylated, and unstable RNAs known as PROMPTs (promoter upstream transcripts) arise from divergent transcription at bidirectional promoters (Preker et al 2008(Preker et al , 2011Jensen et al 2013;Ntini et al 2013). Transcription in the upstream antisense direction is thought to be nonproductive because cryptic pA signals induce termination, and the resulting RNAs are degraded by the nuclear exosome.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] In many cases, antisense transcripts upstream of promoters are unstable and their emergence might be explained by aberrant transcription initiation of RNA polymerase II due to the depletion of nucleosomes on active promoters. 14,[17][18][19][20] In evolutionary terms, divergent transcription initiation could fuel the emergence of new functional genes, by exposing the transcribed DNA strand to mutagenic alterations as has been reported for the acquisition of splice sites. 21 Several studies have addressed the regulation of bidirectional transcription, 13,16,18,19,[22][23][24][25][26][27] with three of these shedding light on the functionality of ncRNAs that are bidirectionally expressed from human PCG promoters: Hung et al 28 investigated human cell cycle-regulated genes and identified 58 functional long ncRNAs that are co-expressed with PCGs from bidirectional promoters.…”
Section: Introductionmentioning
confidence: 86%
“…Additionally, promoter upstream transcripts (PROMPTs) are largely unaffected by Xrn2 (our unpublished findings). This is despite observations that PROMPTs are relatively rich in PAS’s with evidence that these are sometimes functional [23]. Thus, RNA cleavage does not automatically trigger Xrn2-dependent RNA degradation and termination.…”
Section: The Role Of Xrn2 In Termination At Other Pol II Gene Classesmentioning
confidence: 95%